(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The problem of the research was the lack of interest of the Iraqi private commercial banks sufficiently in studying the credit ability of customers and collecting information about them, which makes the process of granting credit permeated with many risks, and the soundness of decision-making by the bank’s management). Exchanging credit information about the customer by the bank before granting credit in the efficiency of cash credit granting decisions? The research also aimed to define the role of banking inquiry and the exchange of credit information in enhancing the efficiency of the credit decision taken by the banking system, in order to ensure the safety of payment and non-defaulting. Of a total of (34) banks listed in the Iraq Stock Exchange, which are (Al-Ahly Bank of Iraq, Middle East, United Investment, Assyria International, Commercial Gulf, Sumer Commercial, Babel), and the use of the statistical program (SPSS V.25) in the analysis of the tool Research (questionnaire) and testing research hypotheses. The research reached a set of results, the most important of which are: the presence of a significant effect relationship of the variable of the credit inquiry system on the variable of creditworthiness, with its dimensions (customer’s capital, the customer’s financial ability, the guarantees provided, the surrounding circumstances), and no effect relationship on the dimension (the customer’s personality ) .